Evaluation of energy uses for two types of holing method / Muhammad Ridhwan Suhaimi - Suhaimi, Muhammad Ridhwan (Faculty of Plantation and Agrotechnology, 2017)
The replanting operation of an oil palm as a whole need to meet the timeline provided. As holing is one of the processes in replanting operation, it is also important to complete it on time. Holing can be done either manually or mechanically. This study was conducted to evaluate the energy uses in two types of holing methods. Other than energy, the working performance over time and cost that involved in both methods was also evaluated. The data is taken at FGV Tembangau 7. The parameter taken was the food consumption of the labor, the amount of fuel used by the tractor, the area covered within a time, and the cost that involved the two methods of holing. The data then been analyzed using a formula to determine the energy usage. The result showed that the energy consumption by the labor which taken from the energy content of each food they eat is 6.388 MJ and the amount of fuel used by the tractor is 244.20 MJ. The labor can covered 0.72 hectare per day and the auger can covered 3.26 hectare in the same working hour. The cost of paying labor wages is RM 70 per day where the cost of using mechanically is RM 495 per day. It can be concluded that mechanical method is better than manual method. Many companies can use this case study to gain information and to make decision in choosing which method they could use in their plantation.